Clinical outcomes of a novel presbyopia-correcting soft contact lens with a small aperture. Issue 5 (October 2020) - Jun, Ikhyun; Cho, Jin Seok; Kang, Min Gu; Lee, Geun Young; Kim, Eung Kweon; Seo, Kyoung Yul; Kim, Tae-im
Highlights: The newly developed presbyopia-correcting soft contact lens improved distance-corrected near visual acuity. The binocular corrected distance visual acuity was not affected by the pinhole contact lens. Although, some discomfort was present, overall satisfaction level was high. The results suggest that Eyelike Pinhole II is useful for presbyopia correction. Abstract: Purpose: To investigate the efficacy and safety of a newly developed pinhole soft contact lens (Eyelike Pinhole II; Koryo Eyetech Co. Ltd.) for presbyopia correction. Methods: This prospective clinical study enrolled 29 patients with presbyopia between October 2018 and December 2018. All participants wore the Eyelike Pinhole II in the non-dominant eye for >3 h/day for a period of 1 week. Binocular and monocular uncorrected near visual acuities, distance-corrected near visual acuity (DCNVA), uncorrected distance visual acuity, and corrected distance visual acuity (CDVA) were measured before and after the intervention. All visual acuities were measured in logarithm of the minimal angle of resolution (logMAR) units. In addition, binocular defocus curves were generated, and contrast sensitivity values were obtained under photopic and mesopic conditions before and after lens wear. Results: The mean DCNVA of the treated eye and the mean binocular DCNVA improved from 0.34 ± 0.12 to 0.15 ± 0.14 (P < 0.001) and 0.31 ± 0.13 to 0.11 ± 0.10 (P < 0.001) logMAR, respectively, after pinhole contact lens wear. Although the mean CDVA of the treated eye deteriorated from −0.04 ± 0.05 to 0.02 ± 0.11 logMAR (P = 0.015), there was no significant change in the mean binocular CDVA (P = 0.79). The binocular defocus curve showed a significant improvement from −5.0 dioptres (D) to −1.0 D after pinhole contact lens wear. Conclusions: The newly developed Eyelike Pinhole II soft contact lens showed safe and effective outcomes; thus, it could be a promising option for the treatment of presbyopia.